2017
DOI: 10.1016/j.clae.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical fitting characteristics of typical soft contact lens designs

Abstract: Mathematical modelling is a useful method for testing SCL design combinations. The results suggest that judicious choice of additional fittings can expand the range of fitting success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Kollbaum [9] has suggested that further investigation of supplemental power change may be essential to achieve predictable and optimised lens design performance. This corroborates well with the recent work of Sulley et al demonstrating the wide variation in theoretical fitting success rates of soft contact lenses (61% - 90%) despite a narrow range of parameters varying between commercial designs (Base curve radius 8.4 mm to 9.0 mm, and D from 13.8 mm to 14.3 mm) [10]. Historically, changes to optical power from corneal conformance have been estimated roughly.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Kollbaum [9] has suggested that further investigation of supplemental power change may be essential to achieve predictable and optimised lens design performance. This corroborates well with the recent work of Sulley et al demonstrating the wide variation in theoretical fitting success rates of soft contact lenses (61% - 90%) despite a narrow range of parameters varying between commercial designs (Base curve radius 8.4 mm to 9.0 mm, and D from 13.8 mm to 14.3 mm) [10]. Historically, changes to optical power from corneal conformance have been estimated roughly.…”
Section: Introductionsupporting
confidence: 88%
“…al. [10], it was identified that the biggest opportunity for achieving a soft contact lens fitting success was to increase the lens diameter, hence improving corneal coverage. Lenses tested in Sulley et.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, an ellipto-conical corneal modelling of soft lens fit showed closer concordance with actual measurements than an elliptical model and estimated an edge strain of 2.7% for a standard 8.6 mm base curve, 14.2 mm diameter lens on an average eye, with edge strain <0% being too loose and >6% being too tight [326,349]. This modelling showed that theoretical success rates for one base curve would be 61-90% with not much improvement from a second base curve [350]. Increasing lens diameter to >2 mm more than the HVID does not negatively impact the eye if the base curve is adjusted to keep the sag the same [327].…”
Section: Modelling Of Lens Movementmentioning
confidence: 53%
“…In soft contact lens design, the peripheral zone is a specific region connecting the optic zone to the edge profile. This zone is substantial in contact lens fitting; it has been shown that the peripheral corneal shape has a more significant role in successful contact lens wear than the central radius of curvature of the cornea [3,4]. Also when a soft contact lens is fitted to a cornea, it is the peripheral zone that flexes and deforms most [5] which may then influence the optic zone, to which it is connected.…”
Section: Introductionmentioning
confidence: 99%